An Investigation of Pre-service Mathematics Teachers’ TPACK Using the Revised Techno-Pedagogical Integration Matrix - AKKOÇ, HATİCE; HANGÜL, TUĞBA; ÇEZİKTÜRK, ÖZLEM (My University, 2022)
This study investigates pre-service mathematics teachers’ (PMTs) TPACK (Technological Pedagogical Content Knowledge) in the context of their micro-teaching practices. We explored pedagogical purposes for technology integration using a revised version of a two-dimensional model called Techno-Pedagogical Integration Matrix (TPIM) to explore PMTs’ TPACK. We used the Mathematical Quality Instruction (MQI) framework as the x-axis and the SAMR Model (Substitution, Augmentation, Modification, Redefinition) for technology integration as the y-axis of the TPIM. We conducted a case study with four PMTs enrolled in a mathematics teacher preparation program in Istanbul, Turkey. Data consist of video recordings of their micro-teaching lessons. Findings showed that PMTs used technology mainly at the modification level, and none of them reached the redefinition level. In terms of mathematical pedagogy that we explored using the MQI sub-codes, PMTs integrated technology into their lessons to make mathematical explanations, patterns and generalizations, mathematical sense-making, and linking multiple representations. Employing the TPIM, we bring the mathematical pedagogy aspect of the TPACK framework and a detailed exploration of the SAMR model into play. We will discuss theoretical implications regarding using the TPIM and practical implications for developing TPACK in pre-service and in-service teacher education.